Narrating atrocity: Uses of evidence in the political asylum process - Amy Shuman; Carol Bohmer (Danish Institute for International Studies (DIIS), 2010)
Political asylum is one remedy for human rights abuses. By offering safe haven to people fleeing persecution in their homelands, countries providing political asylum acknowledge that violence can make some places too dangerous for members of particular groups. Asylum and human rights' discourses have run on parallel tracks in the post-World War II period, with the initial international recognition of human rights in 1948 (The Universal Declaration of Human Rights), followed by the1951 Refugee Convention. From the beginning, it was important that asylum law not conflict with the sanctity of the sovereign state. As a result, the treaties provide neither the means nor the political mandate to protect people from human rights abuses which are internal to sovereign states. Instead, asylum and refugee law provides one rather piecemeal and ineffective method of addressing such human rights abuses. It addresses human rights abuses on an individual basis and does not apply to many of those who, it could be argued, suffer from such abuses. Accordingly, it is a band aid rather than a potential solution to the problem of human rights, though it may serve the purpose of alerting the world to the existence of human rights abuses in a particular state. In this paper, Amy Schuman and Carol Bohmer explore the disconnect between asylum law and human rights at two levels. First, the relationship between written documentation and oral narrative testimony in political asylum hearings is examined as genres of representation that display and rely on different norms of evidence. Second, it is considered how these evidentiary differences exacerbate the impossible subjectivity of the asylum seeker, whose success in the process depends upon proving that she is who she says she is and that the atrocities she describes really happened. The paper also examines the question of when human rights should outweigh cultural traditions. What may be a human rights violation may not be grounds for asylum in such cases.
Keywords: 330